2017
DOI: 10.1177/1079063217716442
|View full text |Cite
|
Sign up to set email alerts
|

Between the Pew and the Pulpit: Can Personality Measures Help Identify Sexually Abusive Clergy?

Abstract: There has been limited conclusive research examining the personality characteristics of clergy who perpetrate abuse. To address this dearth of research, the current study aimed to develop a personality profile that distinguishes clergy members who sexually abuse children from other clergy. Personality and psychopathology were assessed using the Minnesota Multiphasic Personality Inventory-2 (MMPI-2) and the Millon Clinical Multiaxial Inventory-III (MCMI-III). Data were analyzed from a sample of clergy members, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Homosexuality, however, has not been regarded as contributing significantly in the choice of a male victim (Holt & Massey, 2013; Parkinson et al, 2012). Research on personality characteristics of clergy who perpetrated abuse revealed that clerics who sexually abused children differed from other clergy members only on the Aggressive/Sadistic scale of the Millon Clinical Multiaxial Inventory-III (Amrom et al, 2017). Content analysis of personnel files of accused priests indicated that many priests denied responsibility and justified their sexually abusive behaviors (Spraitz & Bowen, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Homosexuality, however, has not been regarded as contributing significantly in the choice of a male victim (Holt & Massey, 2013; Parkinson et al, 2012). Research on personality characteristics of clergy who perpetrated abuse revealed that clerics who sexually abused children differed from other clergy members only on the Aggressive/Sadistic scale of the Millon Clinical Multiaxial Inventory-III (Amrom et al, 2017). Content analysis of personnel files of accused priests indicated that many priests denied responsibility and justified their sexually abusive behaviors (Spraitz & Bowen, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The sexual abuse crisis represents a watershed moment for the Catholic Church, demanding a full appraisal of the utility and effectiveness of all methods for assessing candidates for the priesthood and religious life (Amrom et al, 2019; John Jay College, 2011; Mihura et al, 2019). In a groundbreaking statement, Pope Francis recently urged that the Church include psychological screening as an essential part of its assessment of candidates and a vital prevention tool in safeguarding against abuse (Zauzmer, 2019).…”
mentioning
confidence: 99%
“…In terms of using the MMPI-2 to identify trends or indicators of sexual offending, Plante and Aldridge (2005) found that Catholic clergy who had been reliably accused of sexual offenses had higher scores on scales related to perceived isolation and frequently experienced greater feeling of distrust with others and preferring social isolation. However, subsequent studies of the MMPI-2 did not support these clear pathological differences between cleric sex offenders and nonoffenders, which led some to call into question the utility of the MMPI-2 as an assessment tool for clergy applicants (Amrom, Calkins, & Fargo, 2019). These mixed findings, as well as other studies of Catholic clergy perpetrators (e.g., Montana et al, 2012), have generally challenged the assumption that sexual offenders will exhibit elevated or different psychopathological traits compared to nonoffenders on the MMPI-2.…”
Section: Mmpi-2 and Mmpi-2-rf Testing Of Clergy Applicantsmentioning
confidence: 99%
“…For example, victims were often altar servers and children in the parish from families with whom priests had built trusting relationships over time. Reinforcing the "acquaintance offender" model among Catholic clergy are some psychological data that has indicated that clergy sexual offenders do not fit into a heterogeneous mold and have not exhibited significantly different psychological profiles from nonoffenders (Amrom et al, 2019). Thus, it is important to emphasize that clergy applicants may exhibit characteristics perceived as normative and adaptive while also having underlying risk factors that are associated with sexual offending.…”
Section: Conceptualizing Catholic Clergy Applicants As "Acquaintance ...mentioning
confidence: 99%